Early Viral Clearance Among Covid-19 Patients When Gargling With Povidone-iodine And Essential Oils: A Clinical Trial - Nurul Azmawati Mohamed; Nizam Baharom; Zetti Zainol Rashid; Wong Kon Ken; Umi Kalsom Ali; Siti Norlia Othman; Muttaqillah Najihan Samat; Najma Kori; Petrick Periyasamy; Nor Azizan Zakaria; Agni Nhirmal Kumar Sugurmar; Nur Ezzaty Mohammad Kazmin; et al. (Japan Health Sciences University, 2024)
Indexed by ERA